Modified enzyme immunoassay for detecting Neisseria gonorrhoeae antigens. - Papasian, C J (1984)
A commercial modification of an enzyme immunoassay (EIA) (Gonozyme; Abbott Laboratories, North Chicago, Ill.) for detection of Neisseria gonorrhoeae antigens was compared with conventional culturing. Specimens from males and females were collected at a sexually transmitted disease clinic; additional female specimens were collected at an obstetrics and gynecology clinic. EIA sensitivity and specificity for males were 100 and 98.6%, respectively (68 negative, 34 positive, 1 false-positive, and 0 false-negative). EIA sensitivity and specificity for female sexually transmitted disease clinic patients were 74.4 and 95.7%, respectively (66 negative, 29 positive, 3 false-positive, and 10 false-negative) EIA sensitivity and specificity for obstetrics and gynecology clinic patients were 100 and 99.2%, respectively (6 positive, 119 negative, 1 false-positive, and 0 false-negative). In female patients from whom multiple swab specimens were collected, the sequence of specimen collection and subsequent EIA analysis affected sensitivity.